Intervención artística acerca de la desvalorización del juego tradicional en la provincia de El Oro - Flores Bustamante, Betty Elizabeth (2018)
The man from his origin has created his ideologies determining an own identity, where he relates and shares customs; but with the evolution our traditions have been lost, one of the possible causes that caused the industrial, economic development and the homogenization of the cultures, in front of this, the society has displayed a series of inappropriate habits that have transformed their cultural profile. At present, the cultural phenomenon has turned society into a vain population, underestimating its roots in the way that its historical review is unknown, therefore the current generation is unprotected of its identity. As a fundamental part of these traditions are the autochthonous ludic activities that are changing as a result of a technological process, as will be discussed later, children as a result of this phenomenon are part of this vice of technology, adopting foreign manners and cultural linguistics. Today's society is manipulated by a system that aims to link with other communities for the exchange of products and ideas, with the power of globalization, this has been generating changes both globally and locally, modifying customs, traditions, forming a single culture. Modern games have been accepted without any limit, leaving traditional games in oblivion, offering the child an inappropriate development, losing interest in knowing their environment, developing their imagination and socializing with other children. The bad influence of these consoles has reached a point that people have ceased to belong to their own space, due to the lack of control and responsibility in the use of these computers, causing problems of anxiety and misbehavior in infants. The purpose of the artistic proposal is to reflect the loss of identity due to technology, with the objective of involving the public and becoming aware of this social problem through artistic intervention, which it has direct contact with the viewer. Considering art as an expression to reflect the environment, through artistic intervention, which consists of developing a technological game as a critic while at the same time giving an inverse function of its ideology, allowing children to have fun, develop their skills and socialize. The research work determines a problematic that seizes the Orense identity by emerging foreign cultural features, causing a decline in the games of yesteryear, therefore it has been considered important to reflect before an artistic manifestation the social fact, being the children a fundamental part of the work and being them the main affected by this modern system. The study mentions contemporary artistic works such as Toshiko Horiuchi, who has promoted the practice of games as a distraction and enjoyment of the family environment. Likewise, we expose another artist for example Saskia Gamboa, who assimilates the theme of the loss of cultural identity, among other artists are also cited such as philosophical authors for the construction of the theoretical bases in the research work.